2021
DOI: 10.9734/ajahr/2021/v8i430126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Turmeric (Curcuma longa L) Genotypes for Growth and Yield Attributes in Plains of Eastern Nepal

Abstract: An experiment was conducted in order to identify the productive genotype of turmeric for the plains of Nepal. In 2017 and 2018, seven promising turmeric genotypes (CI 0207, CI 0205, CI 9102, CI 1312, CI 0503, CI 0507, and CI 0201) were compared with KKH-1 in a Randomized Complete Block Design with four replications at the Directorate of Agricultural Research, Tarahara, Nepal. The plants were 30 cm x 30 cm apart, with 40 plants per 3.6 m2 plot area. Cultural practices were followed in accordance with the recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
4
1
Order By: Relevance
“…The mean leaf count recorded at harvest stands at 8.93. In contrast, Chapagain et al (2021) reported leaf count of just 7.69 slightly lower results compared to our findings. The highest leaf count observed in our study could be attributed to various factors, including differences in soil fertility, climatic conditions, cultivation techniques, and varietal disparities, all of which influence leaf development and overall plant vigor.…”
Section: Effects Of Different Sources Fertilizers On Vegetative Growt...contrasting
confidence: 99%
See 3 more Smart Citations
“…The mean leaf count recorded at harvest stands at 8.93. In contrast, Chapagain et al (2021) reported leaf count of just 7.69 slightly lower results compared to our findings. The highest leaf count observed in our study could be attributed to various factors, including differences in soil fertility, climatic conditions, cultivation techniques, and varietal disparities, all of which influence leaf development and overall plant vigor.…”
Section: Effects Of Different Sources Fertilizers On Vegetative Growt...contrasting
confidence: 99%
“…Turmeric (Curcuma longa L.) is a perennial herbaceous plant belonging to the ginger family, Zingiberaceae (Ferdous et al, 2018), extensively cultivated in the tropical and subtropical regions of the world, including Nepal (Baral et al, 2021;Chandana et al, 2024a). It holds significant cultural, culinary, and medicinal value (Chapagain et al, 2021), with its rhizomes being prized for their vibrant color, Flavors, and therapeutic properties (Hossain et al, 2007). Turmeric has been cultivated across diverse ecological zones of Nepal, spanning from the eastern to western regions, encompassing the inner terai, foothills, and mid-hills up to an altitude of 1600 meters above sea level (Mehata et al, 2022a;Rajbanshi et al, 2023;).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation by GGE biplot of seven turmeric genotypes from Nepal was performed to identify traits helpful in turmeric selection. A total of 71.91% variation was observed from the two principal components (PC1 and PC2), among which 39.08% and 32.83% variation was exhibited by PC1 and PC2, respectively [ 46 ]. Another study in Curcuma angustifolia was carried out to identify a high-yielding stable genotype.…”
Section: Discussionmentioning
confidence: 99%